Pelatihan Manasik terhadap kepuasan jamaah umroh di PT. Ya An Nahl Tour and Travel Kota Malang - Sari, Agustin Puspita; Rahmadian, Aprilia; Lasarudin, Alwin; Yulianto, Irwan (Jurnal Pariwisata Tourista, 2025)
PT. Ya An Nahl Tour is one of the travel in the city of Malang that provides Umrah and Hajj departure services. PT. Ya An Nahl Tour itself has now entered its 15th year and is one of the travel companies that has experienced quite rapid development. Training is the process of teaching the skills needed to do a job. Training will be successful if the identification of training needs is carried out correctly. This research was conducted to determine the effect of training on the satisfaction of Umrah pilgrims in tour and travel in Malang City. The purpose of this study was to analyze and describe the effect of training on the satisfaction of Umrah pilgrims at PT. Ya An Nahl Malang City Tour. The method used in this study is to use a quantitative method with a descriptive approach. The data collection technique is by distributing questionnaires and data obtained from distributing questionnaires using a Likert scale. The results of this study indicate that training has a positive and significant effect on pilgrims' satisfaction and training is the main factor that has a significant effect on Umrah pilgrims' satisfaction.